2014
DOI: 10.1096/fj.14-259366
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of tyrosine 285 of PAK1 facilitates βPIX/GIT1 binding and adhesion turnover

Abstract: The p21-activated serine-threonine kinase (PAK1) regulates cell motility and adhesion. We have previously shown that the prolactin (PRL)-activated tyrosine kinase JAK2 phosphorylates PAK1 in vivo and in vitro and identified tyrosines 153, 201, and 285 in PAK1 as sites of JAK2 tyrosyl phosphorylation. Here, we further investigate the role of the tyrosyl phosphorylated PAK1 (pTyr-PAK1) in regulation of cell adhesion. We use human breast cancer T47D cell lines that stably overexpress PAK1 wild type or PAK1 Y3F mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 120 publications
(190 reference statements)
0
19
0
Order By: Relevance
“…Immunoprecipitation, PAK1 in vitro kinase assay and gene silencing were performed as described in [21]. Briefly, IP’d PAK1 was subjected to an in vitro kinase assay in the presence of 10 μCi of [γ- 32 P]ATP and histone H4 (substrate of PAK1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoprecipitation, PAK1 in vitro kinase assay and gene silencing were performed as described in [21]. Briefly, IP’d PAK1 was subjected to an in vitro kinase assay in the presence of 10 μCi of [γ- 32 P]ATP and histone H4 (substrate of PAK1).…”
Section: Methodsmentioning
confidence: 99%
“…Tyrosyl phosphorylation of PAK1 (pTyr-PAK1) enhances PAK1 kinase activity and its ability to form protein/protein interactions. Both PAK1 activities are important for PRL-dependent breast cancer cell adhesion, motility, and invasion [19,20,21]. pTyr-PAK1 also regulates PRL-induced cyclin D1 promoter activity [22].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that α-MSH activates the Tyrkinase JAK2 (18), which in turn activates PAK1 by the phosphorylation at Tyr 285, (instead of Thr 423), leading to the PIX-PAK1 interaction (19). This could explain why neither α-MSH-dependent activation of PAK1 nor melanogenesis involves the autophosphorylation of PAK1 at Thr 423.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosyl phosphorylation of PAK1 (pTyr-PAK1) enhances such important PAK1 functions as kinase activity and the ability to form protein/protein interactions that are important for adhesion, motility, and invasion of breast cancer cells in response to PRL ([14,15,16]; reviewed in [17]). We have also previously demonstrated that the three tyrosines on PAK1 molecules and PAK1-Nck interaction play a critical role in PAK1-dependent regulation of cyclin D1 promoter activity in response to PRL [18].…”
Section: Introductionmentioning
confidence: 99%